POLYMORPHISMS OF THE CYP1A1, CYP1A2, CYP19, AND SULT1A1 GENES ARE NOT ASSOCIATED WITH INFERTILITY IN WOMEN WITH GENITAL ENDOMETRIOSIS - LARISA N. Danilova; VITALIY O. Chervov; NATALIA V. Artymuk; LYUDMILA A. Gordeeva (Фундаментальная и клиническая медицина, 2018)
Aim. To estimate whether CYP1A1, CYP1A2, CYP19, SULT1A1 gene polymorphisms are associated with genital endometriosis in infertile women. Materials and Methods. We evaluated allele frequencies of aforementioned gene polymorphisms in 100 consecutive women with genital endometriosis-associated infertility and 100 women with tubal infertility utilizing polymerase chain reaction-restriction fragment length polymorphism. Results. We did not find any statistically significant associations between the polymorphisms within the CYP1A1, CYP1A2, CYP19, SULT1A1 genes and genital endometriosis in infertile patients. Conclusions. Further studies are needed to explore the genetic risk factors associated with endometriosis-associated infertility.